2018
DOI: 10.2174/1874434601812010058
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Pictures of Nature and Soft Music on Anxiety and Well-Being During Elective Surgery

Abstract: Background:Patients going through surgery being awake often have a sense of anxiety and need support to relax.Objective:The aim of this study was to investigate whether looking at pictures of natural scenery could reduce anxiety and pain and increase relaxation and well-being being awake during the elective surgery.Methods:This three-arm, randomized intervention study consisted of one group viewing pictures of natural scenery, one group listening to soft instrumental music, and one control group without distra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…A total of 1524 titles and abstracts were screened after removal of duplicates and 154 articles were assessed full text. Fifty-five studies (4968 patients) were included in the qualitative synthesis and 33 studies (2390 patients) 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 in the meta-analysis (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 1524 titles and abstracts were screened after removal of duplicates and 154 articles were assessed full text. Fifty-five studies (4968 patients) were included in the qualitative synthesis and 33 studies (2390 patients) 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 in the meta-analysis (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies provided insufficient details to assess selection bias (14 studies, 25%). 20 22 26 27 28 30 32 36 38 40 59 60 61 62 A moderate to high risk of performance bias was present, as blinding of patients for the music intervention is only possible when the intervention is performed solely intraoperatively during general anesthesia. Blinding of personnel can theoretically be achieved by using headphones for all patients, but is more difficult in practice when patients are free to change music tracks or adjust the volume.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations were recorded from studies involving music intervention during surgery with promising results in the reduction of anxiety levels post-surgery. [25][26][27] On comparing the mean difference of anxiety levels between the two groups, a higher difference was observed in the control group but was statistically insignificant at baseline -10 minutes time interval but was statistically significant (p<0.01) at baseline -20 minutes and 10 minutes -20 minutes. This could be due to the baseline anxiety levels being dissimilar between the two groups and also by giving the patients a choice to choose the music from the list provided to them rather than allowing them to choose a music genre of their personal choice in the experimental group.…”
Section: Discussionmentioning
confidence: 95%
“…The study of Jung et al (2020) [39] on children aged 5-12 years scheduled for elective surgery showed that the use of audiovisual distraction using a visual distraction headset during the induction of general anesthesia in the operating room reduced pediatric preoperative anxiety with a 14.5-point score compared to the control group. Nielsen et al (2018) [40] found that watching natural pictures with the calm green vegetation of landscapes without animals where each one was shown for 45 s and listening to soft instrumental music from the MusiCure collection while being awake after an elective surgery reduced patients' anxiety and pain. It is believed that processing information by the individual's brain is limited.…”
Section: Discussionmentioning
confidence: 99%